Meta Analisis Studi Ulumul Qur’an Di Indonesia (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2021)
One of the strengths that plagued the study of the Ulumul Quran in Indonesia is the textuality of the Koran, which is only able to reproduce the debate around the issue of reconstruction of the Ulumul Quran in the classical to contemporary eras. With a meta-analysis, this tendency seems to override another important issue in the study of the Qur'an in Indonesia, namely the Qur'an in the academic world. This paper aims to explore several alternative trends in the issues of ulumul al-Qur'an in the academic world, arguing that the subject of research in the study of the Qur'an in Indonesia should be humans, not the Qur'an itself. Through this exploration, it is hoped that the research methodology and research object of the study of the Qur'an will increase with various data and take an important role in the shift in Islamic studies in the world.